Doing Bad to Feel Better? An Investigation of Within- and Between-Person Perceptions of Counterproductive Work Behavior as a Coping Tactic - Shoss, Mindy K. (Journal of business ethics, 2016)
Employee counterproductive work behavior (CWB, e.g., theft, production deviance, interpersonal abuse) is costly to organizations and those who work within them. Evidence suggests that employees are motivated to engage in CWB because they believe that these behaviors will make them feel better in response to negative workplace events. However, research has yet to consider the situational and individual factors that shape the extent to which employees view CWB in such a manner. In order to provide insight into the decision-making process surrounding the use of CWB as a coping strategy, this study leverages coping theory to examine the factors (both situational/within-person and individual/between-person) that contribute to employees’ beliefs that CWBs will be instrumental for emotion regulation aims in response to workplace stressors. In a repeated measures scenario-based study of 297 employees, we found that individuals’ perceived coping instrumentalities for CWBs are a function of the controllability and source of the stressor as well as a more stable learned response to stressful situations at work.